International and National Legal Protection of the Civilian Population During an Armed Conflict: The Example of Ukraine - Streltsova, Yevdokiia J.; Streltsov, Yevgen L. (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The protection of civilians is a basic ethical, strategic, and legal requirement for the international community and every democratic state, one of the key aspects of any military (combat) action. Such protection should not only be proclaimed, but also serve as a priority. If armed forces during armed conflicts rely on the foundation laid by international humanitarian law and adhere to civilised rules of military (combat) operations, then the damage caused to the civilian population can be minimised. This problem is also important in terms of the international and national legal protection of the civilian population during the international military conflict in Ukraine.